Intelligence support for EU security policy: Options for enhancing the flow of information and political oversight - Raphael Bossong (Stiftung Wissenschaft und Politik (SWP), 2018)
Since 2015, security cooperation between European Union (EU) member states has progressed at an accelerated pace. For the Union's foreign, security, and defence policy, there is the prospect that increased cooperation and enhanced arms cooperation will create more international capacity to act. As far as internal security is concerned, the continuing threat of terrorism is spurring the establishment of a "European Security Union" based on an intensive exchange of information between security authorities. In the shadow of these developments is the question of the extent to which European intelligence cooperation should also be promoted. In this particularly sensitive area, no steps towards integration that would attract public attention are to be expected. However, existing approaches to intelligence support for EU security policy should be deepened and better monitored.
Keywords: 320